Structural Phase Transitions of Hybrid Perovskites CH3NH3PbX3 (X = Br, Cl) from Synchrotron and Neutron Diffraction Data - Lopez, Carlos Alberto (2020)
Methylammonium (MA) lead trihalide perovskites, that is, CH3NH3PbX3 (X = I, Br, Cl), have emerged as a new class of light-absorbing materials for photovoltaic applications. Indeed, since their implementation in solar-cell heterojunctions, they reached efficiencies above 23%. From a crystallographic point of view, there are many open questions that should be addressed, including the role of the internal motion of methylammonium groups within PbX6 lattice under extreme conditions, such as low/high temperature or high pressure. For instance, in MAPbBr3 perovskites, the octahedral tilting can be induced upon cooling, lowering the space group from the aristotype Pm3¯m to I4/mcm and Pnma. The band gap engineering brought about by the chemical management of MAPb(Br,Cl)3 perovskites has been controllably tuned: the gap progressively increases with the concentration of Cl ions from 2.1 to 2.9 eV. In this chapter, we review recent structural studies by state-of-the-art techniques, relevant to the crystallographic characterization of these materials, in close relationship with their light-absorption properties.